Effect of using protected linseed in rations on sheep blood hematology - Sudiyono, Sudiyono; Widyawati, Susi Dwi; Hanifa, Aqni; Hadi, Rendi Fathoni; Suprayogi, Wara Pratitis Sabar; Wati, Ari Kusuma; Pawestri, Wari (Universitas Sebelas Maret, 2023)
Objective: Blood is a body fluid that plays a role in transporting oxygen, nutrients, metabolic waste, and serves as a component of the immune system. Its measurable indices such as hematological profile is affected by the food consumed. This study aimed to examine the linseed use in complete feed on the hematology value of sheep blood.Methods: This research was conducted at the “Mitra Karya Farm” in Purworejo Village, Gemolong District, Sragen Regency. There were 15 male Fat-Tailed Sheep crossing 1-1.5 years old with an average body weight of 22+2.04 kg as experimental animals. The treatments applied were P1: 100% complete feed, P2: 90% complete feed and 10% linseed, P3: 90% complete feed and 10% linseed meal, P4: 90% complete feed and 10% linseed protected with tannin, and P5: 97% complete feed and 3% linseed oil that are saponified. A one-way, Completely Randomized Design (CRD) was used, and blood hematology was the measured variable, which includes the determination of erythrocytic series (red blood cells, hemoglobin, hematocrit, and erythrocyte index), leukocytes, and platelets.Results: The results showed that the treatment applied had no significant effect on red blood cells value and erythrocyte index, but had a significant effect on hemoglobin, hematocrit, leukocytes, and platelets value. The highest sheep blood Hb (P<0.05) was P3, which did not differ from P4, P1, and P2, while P5 had the lowest Hb level. The highest blood hematocrit was in P1, and this result was not significantly different from P3 and P4, while P2 and P5 produced low hematocrit. The highest leukocytes were achieved by P4 and were not significantly different from P3. Leukocytes were the lowest at P2 and not significantly different from P1. In contrast, P4 sheep platelets were the highest and not significantly different from P3, P1, and P2, while P5 produced the lowest platelets.Conclusions: This study concludes that the sheep that received complete feed, 90% + 10% linseed meal (P3), had the best hematology.